Linked non-monetary and monetary valuation of basecamp aurora tourism: an Icelandic case study - James David Broome; David Cook; Brynhildur Davíðsdóttir; Benjamin David Hennig (Journal of Outdoor Recreation and Tourism, 2026)

Climate effects of management intensity and rotation length for planted pine systems - Sarah J. Puls; Justin S. Baker; Rachel L. Cook; James L. Rakestraw (Mitigation and Adaptation Strategies for Global Change, 2026)
Managed forests, including plantation systems, play a vital and often underappreciated role in contributing to the global carbon sink and mitigating climate change, and determining the most effective mitigation strategies requires accounting methods that accurately assess the climate effects of forests. We use a dynamic life cycle assessment methodology to compare the climate effects of thirty-six forest management scenarios (varying site productivity, planting density, fertilization, and thinning) with varying rotation lengths for loblolly pine plantations in the southern U.S., including both in situ and ex situ greenhouse gas fluxes. We also evaluate the effectiveness of using only carbon stock estimates to assess the net climate effect of a given management regime relative to radiative forcing metrics. Carbon stocks alone failed to accurately portray the climate effects from different management regimes, emphasizing the need for greenhouse gas accounting methodologies that directly represent the effect of forest management on potential atmospheric warming mitigation efforts. When radiative forcing is used for comparison, our results show that management decisions such as thinning and rotation length should be adjusted based on stand-specific conditions, and that overgeneralized strategies, such as extending rotation lengths, had little effect on net radiative forcing for many scenarios.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Genes Versus Environment: Body Size Variation Among Recruitment Cohorts of Dungeness Crab - James L. Dimond; Sarah K. Grossman; Emily V. Buckner; Claire E. Cook; Katelyn M. Bosley; Elizabeth D. Tobin; Julie S. Barber (Molecular Ecology, 2026)
Understanding the drivers of phenotypic variation is key to disentangling the evolutionary and environmental forces that shape patterns of trait variation within and among populations. In Dungeness crab, settlement‐stage megalopae exhibit striking seasonal variation in body size, with early season cohorts consistently larger than later ones. This pattern may result from genetically distinct larval sources or environmentally induced plasticity following the temperature–size rule, which predicts larger body size at cooler temperatures. Here, we evaluated the relative contributions of these potential drivers by analysing megalopae size, regional sea surface temperatures and whole‐genome resequencing data from megalopae collected across the ~5‐month settlement season throughout Washington, USA. Genomic analyses revealed a subtle coastal ancestry signal in early‐arriving megalopae, supporting the hypothesis that these megalopae are of coastal origin. Coastal ancestry was associated with larger megalopae, even after accounting for temperature; however, temperature was a stronger predictor, with a standardised effect size more than three times greater than that of ancestry. A genome‐wide association study found no significant associations with megalopae size, suggesting the absence of a strong genotype–phenotype relationship or a lack of statistical power to detect a highly polygenic trait. Together with prior laboratory rearing studies, our findings support a dominant role for environmentally driven plasticity in body size variation. Persistent cohort differences previously observed in juvenile and adult body size raise the possibility that thermal conditions during early life may promote a carryover effect with potentially significant demographic and fishery implications.

Influences of subtle NMDA receptor blockade and allosteric modulation of α5 GABAA receptors on reward-related impulsivity in rats - Jovana Aranđelović; Bojan Batinić; Dishary Sharmin; Danijela Milenković; Đorđe Đorović; V. V. N. Phani Babu Tiruveedhula; James M Cook; Miroslav M Savić (Psychopharmacology, 2026)

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Australian stingless bees exhibit greater sensitivity to dimethoate than Apis mellifera: implications for pesticide risk assessment - Gaurav Singh; James C. Makinson; Mary Finlay Doney; Onyeka Peter Nzie; James M. Cook; Robert N. Spooner-Hart (Pesticide Biochemistry and Physiology, 2026)

Corrigendum to ‘A national-scale preliminary overview study of poly- and perfluoroalkyl substances (PFAS) occurrence in aquatic environments of England, UK’ [Chemosphere 394 (2026) 144804] - R.J. Patel; D.C. Gooddy; B. Marchant; D.J. Lapworth; A. James; M. Cook; K. Darby; T. Besien (Chemosphere, 2026)

Susceptibility to eight common chemical insecticides in Helicoverpa zea populations from the southern United States - Bhavana Patla; Tiago Silva; Shucong Lin; Graham P. Head; Francis P.F. Reay-Jones; Xinzhi Ni; Lina Bernaola; Sebe Brown; Don Cook; James Villegas; Jeffrey A. Davis; Fangneng Huang (Crop Protection, 2026)

Leveraging additional VIIRS information to improve wildfire tracking in the western US - Shane R. Coffield; Tempest D. McCabe; Wilfrid Schroeder; Yang Chen; Rebecca C. Scholten; Elijah Orland; Tianjia Liu; Elizabeth Wiggins; James T. Randerson; Melanie Follette-Cook; Douglas C. Morton (Remote Sensing of Environment, 2026)

The enemy of my enemy is not always my friend: Susceptibility of honey bee to entomopathogenic nematodes - Alihan Katlav; Sitaram Aryal; Manoj Dhakal; Michael Duncan; Clarissa M. House; Uffe N. Nielsen; James M. Cook; Robert N. Spooner-Hart; Markus Riegler (Journal of Invertebrate Pathology, 2026)

A national-scale preliminary overview study of poly- and perfluoroalkyl substances (PFAS) occurrence in aquatic environments of England, UK - R.J. Patel; D.C. Gooddy; B. Marchant; D.J. Lapworth; A. James; M. Cook; K. Darby; T. Besien (Chemosphere, 2026)

Detection of foodborne viruses in berries – State of science and future considerations - Lee-Ann Jaykus; Sabah Bidawid; Albert Bosch; Sophie Butot; Nigel Cook; Sanjay Gummalla; James Lowther; Neda Nasheri; Rosa M. Pintó; Donald W. Schaffner; Magnus Simonsson; Branko Velebit; et al. (Food Control, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Quantifying Fine Sediment Erosion From Unsealed Roads Draining to the Great Barrier Reef Before and After Applying Best Management Practices - Jeffrey Shellberg; David Klye; Jessie Price-Decle; Pedro Russell-Smith; Keith Cook; Tony Peter; Indigo Gambold; James Dobson (Environmental Management, 2026)

Delivering nutrient management impact through farmer-centric research: a systematic review of innovation systems in African smallholder systems - Ivan S. Adolwa; Shamie Zingore; James Mutegi; Matthew McNee; Bolaji A. Akorede; Denver Masidza; T. Scott Murrell; Samuel Mathu Ndungu; Eileen Nchanji; Simon Cook; Thomas Oberthür (Agricultural Systems, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Improved Estimates of Biomass Expansion Factors and Root‐To‐Shoot Ratios: An Approach for Different Forest Types Across a Climatic Gradient in Brazil - Isáira Leite e Lopes; Otávio Camargo Campoe; Geovanni Malatesta Barros; Anny Francielly Ataide Gonçalves; Gabriela Gonçalves Moreira Matzner; Marco Aurelio Figura; Clayton Alcarde Alvares; Fernanda Leite Cunha; Verônica Boarini Sampaio de Rezende; James Stahl; Josiana Jussara Nazaré Basílio; Hyngrid Jaiely Araújo Félix; et al. (Global Change Biology, 2025)
Advancements in the current state of the art of the key drivers of biomass expansion factor (BEF) and the root‐to‐shoot ratio ( R ) are crucial for producing accurate information on forest biomass and carbon stocks. Hence, we compiled a nationally representative dataset encompassing diverse tree growth stages and climatic gradients. In this study, we propose models to improve BEF and R estimates at the tree level for Eucalyptus and Pinus plantations in Brazil. In general, the BEF values were more representative (91.7%) in the database than the R values (8.3%) due to the high cost of collecting coarse roots. Regarding genera, Eucalyptus was more extensively sampled (89.9%) than Pinus (10.1%), reflecting the predominance of Eucalyptus as the most widely planted genus in Brazil. The average BEF and R values calculated in this study were 1.16 and 0.22, respectively, for Eucalyptus spp. and 1.22 and 0.31, respectively, for Pinus spp. In predicting the BEFs, the random effects in the linear mixed model that significantly captured the variations in Eucalyptus and Pinus spp. were temperature and age class, respectively. The fixed effects for Eucalyptus spp. included diameter, height, and age, while for Pinus spp., they were the Köppen climate classification, species, slenderness degree, and age. R estimates were mainly influenced by precipitation and age for both genera, with slenderness and diameter specifically affecting Eucalyptus spp., and height being a driving factor for Pinus spp. Our findings discourage the use of fixed or default values for BEF and R across locations with different climates and growing conditions to reduce uncertainties in carbon accounting and greenhouse gas inventories.

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Canine proliferative sparganosis: a case report and review of larval cestodiasis in dogs - Varvara Semenova; Heather D.S. Walden; Kelsey Bollenback; James R. Cook; Robert J. Ossiboff (Journal of Comparative Pathology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

New opportunities and challenges for conservation evidence synthesis from advances in natural language processing - Charlotte H. Chang; Susan C. Cook‐Patton; James T. Erbaugh; Luci Lu; Yuta J. Masuda; István Molnár; Dávid Papp; Brian E. Robinson (Conservation Biology, 2025)
Addressing global environmental conservation problems requires rapidly translating natural and conservation social science evidence to policy‐relevant information. Yet, exponential increases in scientific production combined with disciplinary differences in reporting research make interdisciplinary evidence syntheses especially challenging. Ongoing developments in natural language processing (NLP), such as large language models, machine learning (ML), and data mining, hold the promise of accelerating cross‐disciplinary evidence syntheses and primary research. The evolution of ML, NLP, and artificial intelligence (AI) systems in computational science research provides new approaches to accelerate all stages of evidence synthesis in conservation social science. To show how ML, language processing, and AI can help automate and scale evidence syntheses in conservation social science, we describe methods that can automate querying the literature, process large and unstructured bodies of textual evidence, and extract parameters of interest from scientific studies. Automation can translate to other research agendas in conservation social science by categorizing and labeling data at scale, yet there are major unanswered questions about how to use hybrid AI‐expert systems ethically and effectively in conservation.

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Insights from the international workshop on “Adapting agriculture to climate change and air pollution” - Evgenios Agathokleous; Lisa Emberson; Jie Pei; Kazuhiko Kobayashi; James D. Blande; Jo Cook; Chao Fang; Zhiyu Han; Hui Ju; Oliver Knopf; Tao Li; Bing Liu; et al. (Environmental Science and Pollution Research, 2024)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Auroral ecosystem services: A cascade model and investigation of co-production processes - James David Broome; David Cook; Brynhildur Davíðsdóttir (Ecosystem Services, 2024)

Intracerebral Administration of a Novel Self-Assembling Peptide Hydrogel Is Safe and Supports Cell Proliferation in Experimental Intracerebral Haemorrhage - Faye Bolan; Ben R. Dickie; James R. Cook; Josephine M. Thomas; Emmanuel Pinteaux; Stuart M. Allan; Alberto Saiani; Catherine B. Lawrence (Translational Stroke Research, 2024)
Intracerebral haemorrhage (ICH) is the deadliest form of stroke, but current treatment options are limited, meaning ICH survivors are often left with life-changing disabilities. The significant unmet clinical need and socioeconomic burden of ICH mean novel regenerative medicine approaches are gaining interest. To facilitate the regeneration of the ICH lesion, injectable biomimetic hydrogels are proposed as both scaffolds for endogenous repair and delivery platforms for pro-regenerative therapies. In this paper, the objective was to explore whether injection of a novel self-assembling peptide hydrogel (SAPH) Alpha2 was feasible, safe and could stimulate brain tissue regeneration, in a collagenase-induced ICH model in rats. Alpha2 was administered intracerebrally at 7 days post ICH and functional outcome measures, histological markers of damage and repair and RNA-sequencing were investigated for up to 8 weeks. The hydrogel Alpha2 was safe, well-tolerated and was retained in the lesion for several weeks, where it allowed infiltration of host cells. The hydrogel had a largely neutral effect on functional outcomes and expression of angiogenic and neurogenic markers but led to increased numbers of proliferating cells. RNAseq and pathway analysis showed that ICH altered genes related to inflammatory and phagocytic pathways, and these changes were also observed after administration of hydrogel. Overall, the results show that the novel hydrogel was safe when injected intracerebrally and had no negative effects on functional outcomes but increased cell proliferation. To elicit a regenerative effect, future studies could use a functionalised hydrogel or combine it with an adjunct therapy.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Wild native insects are efficient pollinators of mangoes in the Northern Territory of Australia - Gaurav Singh; James C. Makinson; Amy M. Gilpin; Robert N. Spooner-Hart; James M. Cook (Agriculture, Ecosystems & Environment, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Remission cytochrome spectroscopy reveals the mode of action of bedaquiline in living mycobacteria - Suzanna H. Harrison; Rowan C. Walters; Morwan M. Osman; Roger J. Springett; Gregory M. Cook; James N. Blaza (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

An analysis of culture-based methods used for the detection and isolation of Salmonella spp., Escherichia coli, and Enterococcus spp. from surface water: A systematic review - Betty R. McConn; Autumn L. Kraft; Lisa M. Durso; Abasiofiok M. Ibekwe; Jonathan G. Frye; James E. Wells; Elizabeth M. Tobey; Stephanie Ritchie; Clinton F. Williams; Kimberly L. Cook; Manan Sharma (Science of The Total Environment, 2024)

Heavenly lights: An exploratory review of auroral ecosystem services and disservices - James David Broome; David Cook; Brynhildur Davíðsdóttir (Ecosystem Services, 2024)

Search for source of invasive-range populations of a haplodiploid pest species reveals Wolbachia-driven mitochondrial selective sweep in native range - Alihan Katlav; Duong T. Nguyen; Asha Chhagan; Lisa Jamieson; Alexander R. Robertson; Jodie Cheesman; Stewart Learmonth; Piotr Trębicki; James M. Cook; Markus Riegler (Journal of Pest Science, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Growth kinetics of Bacillus cytotoxicus in liquid Egg yolk during treatment with phospholipase A2 – A one-step global dynamic analysis - Lihan Huang; Nurul Hawa Ahmad; Vijay Juneja; Erika Stapp-Kamotani; Jose Gabiola; Udit Minocha; Robert Phillips; Marie Hooker; Isabel Walls; Kim Cook; James Lindsay (Food Microbiology, 2024)

Variation in functional composition of reef fishes along a tropical‐to‐temperate gradient - Charlotte G. Clay; James D. Reimer; Brigitte Sommer; Katie M. Cook; Masaru Mizuyama; Masami Obuchi; Iori Kawamura; Hiroki Kise; Maria Beger (Journal of Biogeography, 2024)
Aims Transformation of species and functional composition on subtropical reefs are ongoing due to poleward range shifts of some tropical species, with largely unknown consequences to ecosystem functioning. Trait‐based approaches are powerful tools to quantify such changes. Here, we evaluated changes in the trait composition of coral‐associated fish assemblages along a tropical‐to‐temperate environmental gradient of ca. 1400 km in southern Japan with abundance‐weighted trait expression to assess how trait composition changes with increasing latitude. Location Ryukyu Islands and southern Pacific coast of Japan. Taxon Reef fish. Methods We tested for shifts in trait space and functional redundancy, based on five morphological, life history and behavioural traits: maximum length, pelagic larval duration, trophic level, substrate preference and reproductive mode. Our trait database was coded with two approaches, first, by attributing a single value to each trait per species, and second, by fuzzy coding that allows more than one value per trait and hence considers some intraspecific trait variation. Results We found a reduction in specialist habitat traits (coral substrate preference, nesters and herbivores) and an increase in generalist traits (predators) with increasing latitude, along with a contraction in trait space from tropical‐to‐temperate reefs. Functional redundancy declined with increasing latitude. These trends were closely linked with latitudinal gradients in temperature, along with changes in other environmental factors such as turbidity and photosynthetically active radiation. Main Conclusion Functional turnover and contractions are thus likely due to the marginal conditions for coral‐associated fishes at higher latitudes, favouring generalist species, whereas increased resources at lower latitudes favour high redundancy and niche partitioning. Accounting for intraspecific trait variation indicated the same trends but highlighted increased functional vulnerability across all sites. We show that trait complexity in coral‐associated fish communities decreases from tropical‐to‐temperate reefs, highlighting the reduced functional scope that comes with marginal environmental conditions.

Cecal dilatation in cattle ingesting Megathyrsus maximus (syn. Panicum maximum) cv. Mombaça and cv. Tanzânia - Sandro V. Schons; Taciane Leticia de Melo Souza; Jeronimo Vieira Dantas Filho; Elvino Ferreira; Ed Johnny da Rosa Prado; James Pfister; Daniel Cook; Franklin Riet-Correa (Toxicon, 2024)

Transmission mode predicts coinfection patterns of insect‐specific viruses in field populations of the Queensland fruit fly - Stephen R. Sharpe; Jennifer L. Morrow; James M. Cook; Alexie Papanicolaou; Markus Riegler (Molecular Ecology, 2024)
Insect‐specific viruses (ISVs) can affect insect health and fitness, but can also interact with other insect‐associated microorganisms. Despite this, ISVs are often studied in isolation from each other, in laboratory populations. Consequently, their diversity, prevalence and associations with other viruses in field populations are less known, yet these parameters are important to understanding virus epidemiology. To help address this knowledge gap, we assessed the diversity, prevalence and coinfections of three ISVs (horizontally transmitted cripavirus, biparentally transmitted sigmavirus and maternally transmitted iflavirus) in 29 field populations of Queensland fruit fly, Australia's most significant horticultural pest, in the context of their different transmission modes. We detected new virus variant diversity. In contrast to the very high virus prevalence in laboratory populations, 46.8% of 293 field flies carried one virus and 4.8% had two viruses. Cripavirus and sigmavirus occurred in all regions, while iflavirus was restricted to subtropical and tropical regions. Cripavirus was most prevalent (37.5%), followed by sigmavirus (13.7%) and iflavirus (4.4%). Cripavirus coinfected some flies with either one of the two vertically transmitted viruses. However, sigmavirus did not coinfect individuals with iflavirus. Three different modelling approaches detected negative association patterns between sigmavirus and iflavirus, consistent with the absence of such coinfections in laboratory populations. This may be linked with their maternal transmission and the ineffective paternal transmission of sigmavirus. Furthermore, we found that, unlike sigmavirus and iflavirus, cripavirus load was higher in laboratory than field flies. Laboratory and mass‐rearing conditions may increase ISV prevalence and load due to increased transmission opportunities. We conclude that a combination of field and laboratory studies is needed to uncover ISV interactions and further our understanding of ISV epidemiology.

Factors Influencing Health-Related Quality of Life of Patients with Spinocerebellar Ataxia - Niklas Weber; Maresa Buchholz; Anika Rädke; Jennifer Faber; Tanja Schmitz-Hübsch; Heike Jacobi; Thomas Klockgether; Wolfgang Hoffmann; Bernhard Michalowsky; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; et al. (The Cerebellum, 2024)
Background Little is known about the progression of health-related quality of life (HRQoL) and predicting factors in spinocerebellar ataxia (SCA). Such knowledge is crucial to identify modifiable factors promoting everyday life with SCA and attenuating HRQoL decline. Objectives This study is to assess HRQoL progression and identify factors affecting SCA patients’ HRQoL. Methods Longitudinal data (three-year follow-up) of 310 SCA patients of the European SCA3/Machado-Joseph-Disease Initiative (ESMI) (2016-2022) and 525 SCA patients (SCA1, SCA2, SCA3 or SCA6) of the EUROSCA natural history study cohort (2006–2015) were assessed. Both large cohort studies share standardized assessments of clinical measures, SARA, INAS, PHQ-9, and HRQoL (EQ-5D-3L). The association between HRQoL and clinical measures was assessed by Spearman Correlation (r s ). Multivariable panel regression models were performed to evaluate the impact of patients’ socio-demographics, age of onset, SCA type and body mass index (BMI), and clinical measures on HRQoL progression. Results HRQoL significantly decreased over one (− 0.014, p = 0.095), two (− 0.028, p = 0.003), and three years (− 0.032, p = 0.002). Ataxia severity and mental health strongly correlated with HRQoL (r s SARA = − 0.589; r s PHQ-9 = − 0.507). HRQoL more intensively declined in male (ß = − 0.024, p = 0.038) patients with an earlier age of onset (ß = 0.002, p = 0.058). Higher progression of ataxia severity (ß = − 0.010, p ≤ 0.001), mental health problems (ß = − 0.012, p < 0.001), and higher BMI (ß = − 0.003, p = 0.029) caused more severe decline of patients’ HRQoL over time. Discussion In absence of curative treatments, stronger focus on mental health and weight influence could help clinical evaluation and accompany treatment improving SCA patients’ HRQoL, especially in male patients with early disease onset.

Heat stress survival and thermal tolerance of Australian stingless bees - Scott Nacko; Mark A. Hall; Rosalyn Gloag; Kate E. Lynch; Robert N. Spooner-Hart; James M. Cook; Markus Riegler (Journal of Thermal Biology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Health-Related Quality of Life in Patients with Spinocerebellar Ataxia: a Validation Study of the EQ-5D-3L - Maresa Buchholz; Niklas Weber; Anika Rädke; Jennifer Faber; Tanja Schmitz-Hübsch; Heike Jacobi; Feng Xie; Thomas Klockgether; Bernhard Michalowsky; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; et al. (The Cerebellum, 2023)
Although health-related quality of life (HRQoL) has developed into a crucial outcome parameter in clinical research, evidence of the EQ-5D-3L validation performance is lacking in patients with spinocerebellar ataxia (SCA) types 1, 2, 3, and 6. The objective of this study is to assess the acceptability, validity, reliability, and responsiveness of the EQ-5D-3L. For n = 842 predominantly European SCA patients of two longitudinal cohort studies, the EQ-5D-3L, PHQ-9 (Patient Health Questionnaire), and ataxia-specific clinical assessments (SARA: Scale for Assessment and Rating of Ataxia; ADL: activities of daily living as part of Friedreich’s Ataxia Rating Scale; INAS: Inventory of Non-Ataxia Signs) were assessed at baseline and multiple annual follow-ups. The EQ-5D-3L was evaluated regarding acceptability, distribution properties, convergent and known-groups validity, test-retest reliability, and effect size measures to analyze health changes. The non-item response was low (EQ-5D-3L index: 0.8%; EQ-VAS: 3.4%). Ceiling effects occurred in 9.9% (EQ-5D-3L) and 3.0% (EQ-VAS) with a mean EQ-5D-3L index of 0.65 ± 0.21. In total, convergent validity showed moderate to strong Spearman’s rho ( r s > 0.3) coefficients comparing EQ-5D-3L and EQ-VAS with PHQ-9, SARA, ADL, and INAS. EQ-5D-3L could discriminate between groups of age, SARA, ADL, and INAS. Intra-class correlation coefficients (EQ-5D-3L ICC : 0.95/EQ-VAS ICC : 0.88) and Kappa statistics (range 0.44 to 0.93 for EQ-5D-3L items) indicated tolerable reliability. EQ-5D-3L shows small (effect size < 0.3) to moderate (effect size 0.3–0.59) health changes regarding ataxia severity. The analysis confirms an acceptable, reliable, valid, and responsive recommended EQ-5D-3L in SCA patients, measuring the HRQoL adequately, besides well-established clinical instruments.

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Resiliency of Nuttall oak but not Shumard oak to winter and spring flood: dormancy alone does not confer flood tolerance - Richard D. Sample; James Cook; Benjamin A. Babst (Trees, 2023)

Host insect specificity and interspecific competition drive parasitoid diversification in a plant–insect community - Ai‐Ying Wang; Yan‐Qiong Peng; James M. Cook; Da‐Rong Yang; Da‐Yong Zhang; Wan‐Jin Liao (Ecology, 2023)
Ecological interactions among plants, insect herbivores, and parasitoids are pervasive in nature and play important roles in community assembling, but the codiversification of tri‐trophic interactions has received less attention. Here we compare pairwise codiversification patterns between a set of 22 fig species, their herbivorous pollinating and galling wasps, and their parasitoids. The parasitoid phylogeny showed significant congruence and more cospeciation events with host insects phylogeny than with host plants. These results suggest that parasitoid phylogeny and speciation is more closely related to their host insects than to their host plants. The pollinating wasps hosted more parasitoid species than gallers and indicated a more intense interspecific competition among parasitoids associated with pollinators. Closer matching and fewer evolutionary host shifts were found between parasitoids and galler hosts than between parasitoids and pollinator hosts. These results suggest that interspecific competition among parasitoids, rather than resource availability of host wasps, is the main driver of the codiversification pattern in this community. Therefore, our study highlights the important role of interspecific competition among high trophic level insects in plant–insect tri‐trophic community assembling.

Effect of oviposition delay on early reproductive effort and offspring fitness in a thrips species - Alihan Katlav; James M. Cook; Markus Riegler (Animal Behaviour, 2023)

Microbial diversity in stingless bee gut is linked to host wing size and influenced by the environment - Hongwei Liu; Mark A. Hall; Laura E. Brettell; Juntao Wang; Megan Halcroft; Scott Nacko; Robert Spooner-Hart; James M. Cook; Markus Riegler; Brajesh K. Singh (Journal of Invertebrate Pathology, 2023)

Associations of urinary metabolite concentrations of phthalates and phthalate replacements with body composition from mid-childhood to early adolescence - Lisa B. Rokoff; Shravanthi M. Seshasayee; Jenny L. Carwile; Sheryl L. Rifas-Shiman; Julianne Cook Botelho; Catherine M. Gordon; Russ Hauser; Tamarra James-Todd; Jessica G. Young; Clifford J. Rosen; Antonia M. Calafat; Emily Oken; et al. (Environmental Research, 2023)

Toxic plants from the perspective of a “Quilombola” community in the Cerrado region of Brazil - Ricardo de Castro Santos Paim; Luiza Gabriella Ferreira de Paula; Débora Moreira Soares; Tarik Fernandes Gonçalves Rocha; Amanda Lopes Ribeiro; Natália Barros; Fabrício Carrião dos Santos; Heleno Dias Ferreira; Vera Lúcia Gomes-Klein; Benito Soto-Blanco; José Paes de Oliveira-Filho; Paulo Henrique Jorge da Cunha; et al. (Toxicon, 2023)

Are we there yet? Management baselines and biodiversity indicators for the protection and restoration of subtidal bivalve shellfish habitats - Jose M. Fariñas-Franco; Robert L. Cook; Fiona R. Gell; Dan B. Harries; Natalie Hirst; Flora Kent; Rebecca MacPherson; Colin Moore; James M. Mair; Joanne S. Porter; William G. Sanderson (Science of The Total Environment, 2023)

Integrating knowledge on green infrastructure, health and well-being in ageing populations: Principles for research and practice - Matthew Dennis; Adam Barker; Jamie Anderson; Jenna C. Ashton; Gina Cavan; Penny A. Cook; David French; Anna Gilchrist; Philip James; Christopher Phillipson; Konstantinos Tzoulas; C. Philip Wheater; et al. (Ambio, 2023)
Ageing and urbanisation pose significant challenges for public health and urban planning. Ageing populations are at particular risk from hazards arising from urbanisation processes, some of which are in turn exacerbated by climate change. One approach for mitigating the negative effects of urbanisation on ageing populations is the leveraging of the beneficial effects of urban green infrastructure as a public health intervention in the planning process. We assessed the potential of available theoretical frameworks to provide the context for such leverage. This involved active engagement with academics and practitioners specialising in ageing, green infrastructure and health and well-being through a knowledge-brokering approach. We concluded that an integrated and comprehensive framework on the socio-cultural-ecological determinants of health is lacking. To address this, we present a set of principles for overcoming challenges to knowledge integration when working at the intersection of green infrastructure, ageing, health and well-being. Our findings—and the co-production process used to generate them—have wider significance for trans-disciplinary research into the benefits of the natural environment to human health and well-being as well as other complex and interconnected topics associated with global grand challenges.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Synergistic antihyperalgesic and antinociceptive effects of morphine and methyl 8-ethynyl-6-(pyridin-2-yl)-4H-benzo[f]imidazo[1,5-a][1,4]diazepine-3-carboxylate (MP-III-024): a positive allosteric modulator at α2GABAA and α3GABAA receptors - Mohammad A. Rahman; Thomas M. Keck; Michael M. Poe; Dishary Sharmin; James M. Cook; Bradford D. Fischer (Psychopharmacology, 2021)

Immersion challenge of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. did not increase the severity of Neoparamoeba perurans ‐induced amoebic gill disease (AGD) - Chloe J. English; Natasha A. Botwright; Mark B. Adams; Andrew C. Barnes; James W. Wynne; Paula C. Lima; Mathew T. Cook (Journal of Fish Diseases, 2021)
Amoebic gill disease (AGD) is one of the main health issues impacting farmed Atlantic salmon. Neoparamoeba perurans causes AGD; however, a diversity of other amoeba species colonizes the gills and there is little understanding of whether they are commensal or potentially involved in different stages of gill disease development. Here, we conduct in vivo challenges of naïve Atlantic salmon with cultured Nolandella sp. and Pseudoparamoeba sp. to investigate their pathogenicity to Atlantic salmon gills. Additionally, we assessed whether the presence of Nolandella sp. and Pseudoparamoeba sp. influences the onset and/or severity of N. perurans ‐induced AGD. All three strains attached and multiplied on the gills according to qPCR analysis. Furthermore, minor gross gill lesions and histological changes were observed post‐exposure. While N. perurans was found associated with classical AGD lesions, Nolandella sp. and Pseudoparamoeba sp. were not found associated with lesion sites and these lesions did not meet the expected composite of histopathological changes for AGD. Moreover, the presence of these non‐ N. perurans species did not significantly increase the severity of AGD. This trial provides evidence that cultured Nolandella sp. and Pseudoparamoeba sp. do not induce AGD and do not influence the severity of AGD during the early stages of development.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Low‐coverage genomic data resolve the population divergence and gene flow history of an Australian rain forest fig wasp - Lisa Cooper; Lynsey Bunnefeld; Jack Hearn; James M. Cook; Konrad Lohse; Graham N. Stone (Molecular Ecology, 2020)
Population divergence and gene flow are key processes in evolution and ecology. Model‐based analysis of genome‐wide data sets allows discrimination between alternative scenarios for these processes even in nonmodel taxa. We used two complementary approaches (one based on the blockwise site frequency spectrum [bSFS], the second on the pairwise sequentially Markovian coalescent [PSMC]) to infer the divergence history of a fig wasp, Pleistodontes nigriventris . Pleistodontes nigriventris and its fig tree mutualist Ficus watkinsiana are restricted to rain forest patches along the eastern coast of Australia and are separated into The Northern population is to the north of the Southern populations by two dry forest corridors (the Burdekin and St. Lawrence Gaps). We generated whole genome sequence data for two haploid males per population and used the bSFS approach to infer the timing of divergence between northern and southern populations of P. nigriventris , and to discriminate between alternative isolation with migration (IM) and instantaneous admixture (ADM) models of postdivergence gene flow. Pleistodontes nigriventris has low genetic diversity (π = 0.0008), to our knowledge one of the lowest estimates reported for a sexually reproducing arthropod. We find strongest support for an ADM model in which the two populations diverged ca . 196 kya in the late Pleistocene, with almost 25% of northern lineages introduced from the south during an admixture event ca. 57 kya. This divergence history is highly concordant with individual population demographies inferred from each pair of haploid males using PSMC. Our analysis illustrates the inferences possible with genome‐level data for small population samples of tiny, nonmodel organisms and adds to a growing body of knowledge on the population structure of Australian rain forest taxa.

Effect of blast-related mTBI on the working memory system: a resting state fMRI study - Kathleen F. Pagulayan; Eric C. Petrie; David G. Cook; Rebecca C. Hendrickson; Holly Rau; Melissa Reilly; Cindy Mayer; James S. Meabon; Murray A. Raskind; Elaine R. Peskind; Natalia Kleinhans (Brain Imaging and Behavior, 2020)

Blue carbon gains from glacial retreat along Antarctic fjords: What should we expect? - David K. A. Barnes; Chester J. Sands; Alison Cook; Floyd Howard; Alejandro Roman Gonzalez; Carlos Muñoz–Ramirez; Kate Retallick; James Scourse; Katrien Van Landeghem; Nadescha Zwerschke (Global Change Biology, 2020)
Rising atmospheric CO 2 is intensifying climate change but it is also driving global and particularly polar greening. However, most blue carbon sinks (that held by marine organisms) are shrinking, which is important as these are hotspots of genuine carbon sequestration. Polar blue carbon increases with losses of marine ice over high latitude continental shelf areas. Marine ice (sea ice, ice shelf and glacier retreat) losses generate a valuable negative feedback on climate change. Blue carbon change with sea ice and ice shelf losses has been estimated, but not how blue carbon responds to glacier retreat along fjords. We derive a testable estimate of glacier retreat driven blue carbon gains by investigating three fjords in the West Antarctic Peninsula (WAP). We started by multiplying ~40 year mean glacier retreat rates by the number of retreating WAP fjords and their time of exposure. We multiplied this area by regional zoobenthic carbon means from existing datasets to suggest that WAP fjords generate 3,130 tonnes of new zoobenthic carbon per year (t zC/year) and sequester >780 t zC/year. We tested this by capture and analysis of 204 high resolution seabed images along emerging WAP fjords. Biota within these images were identified to density per 13 functional groups. Mean stored carbon per individual was assigned from literature values to give a stored zoobenthic Carbon per area, which was multiplied up by area of fjord exposed over time, which increased the estimate to 4,536 t zC/year. The purpose of this study was to establish a testable estimate of blue carbon change caused by glacier retreat along Antarctic fjords and thus to establish its relative importance compared to polar and other carbon sinks.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

One week of magnesium supplementation lowers IL-6, muscle soreness and increases post-exercise blood glucose in response to downhill running - Charles James Steward; Yue Zhou; Gary Keane; Matthew David Cook; Yunyi Liu; Tom Cullen (European Journal of Applied Physiology, 2019)

Correction to: Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johanssen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johannsen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Small Animal Multivariate Brain Analysis (SAMBA) – a High Throughput Pipeline with a Validation Framework - Robert J. Anderson; James J. Cook; Natalie Delpratt; John C. Nouls; Bin Gu; James O. McNamara; Brian B. Avants; G. Allan Johnson; Alexandra Badea (Neuroinformatics, 2019)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

α5GABAA subunit-containing receptors and sweetened alcohol cue-induced reinstatement and active sweetened alcohol self-administration in male rats - Cassie M. Chandler; Jaren Reeves-Darby; Sherman A. Jones; J. Abigail McDonald; Guanguan Li; Md T. Rahman; James M. Cook; Donna M. Platt (Psychopharmacology, 2019)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

An ancient and a recent colonization of islands by an Australian sap‐feeding insect - Caroline Fromont; Paul D. Rymer; Markus Riegler; James M. Cook (Journal of Biogeography, 2018)
Aim To assess the genetic structure, biogeography, and the potential for speciation, of a highly host‐specific insect pest with mainland and island populations. Location East coast of Australia, Lord Howe Island ( LHI ), and New Zealand. Methods We focussed on Mycopsylla fici , a plant sap‐feeding insect host‐specific to the fig tree Ficus macrophylla . We genotyped 152 insects from across the natural and extended host plant range at 14 microsatellite loci and analysed the data using standard population genetics statistics, Discriminant Analysis of Principal Components, genetic autocorrelation, and two Bayesian clustering approaches. Results Genetic analyses revealed that the northeastern Australian mainland population (Brisbane) is the centre of genetic diversity. Northeastern and southeastern (Sydney) mainland populations are genetically differentiated and interconnected in a stepping‐stone pattern. The LHI population is the most distinct genetically and Bayesian estimates indicated that the most recent colonization occurred c . 2,000‐17,500 years ago from a northeastern mainland origin. In contrast, the New Zealand population is little differentiated from the Sydney population and probably diverged by colonization within the past 200 years. Main conclusions The strong differentiation in nuclear microsatellites mirrors previous evidence for divergence of the LHI population from both mt DNA and endosymbiont DNA . The LHI population may be undergoing speciation from the mainland populations, with an oceanic barrier to gene flow. In contrast, the geographically isolated population in Auckland represents a far more recent colonization reflecting the contemporary naturalization of the plant host in New Zealand.

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Vegetation changes in blown-down and scorched forests 10–26 years after the eruption of Mount St. Helens, Washington, USA - James E. Cook; Charles B. Halpern (Plant Ecology, 2018)

What shapes plant and animal diversity on urban golf courses? - Sabine S. Nooten; Patrick Schultheiss; Jules Wright; Catriona Macdonald; Brajesh K. Singh; James M. Cook; Sally A. Power (Urban Ecosystems, 2018)

Negative allosteric modulation of alpha 5-containing GABAA receptors engenders antidepressant-like effects and selectively prevents age-associated hyperactivity in tau-depositing mice - Nina Z. Xu; Margot Ernst; Marco Treven; Rok Cerne; Mark Wakulchik; Xia Li; Timothy M. Jones; Scott D. Gleason; Denise Morrow; Jeffrey M. Schkeryantz; Md. Toufiqur Rahman; Guanguan Li; et al. (Psychopharmacology, 2018)

Using basic metrics to analyze high-resolution temperature data in the subsurface - Margaret Shanafield; James L. McCallum; Peter G. Cook; Saskia Noorduijn (Hydrogeology Journal, 2017)

Abuse-related effects of subtype-selective GABAA receptor positive allosteric modulators in an assay of intracranial self-stimulation in rats - Kathryn L. Schwienteck; Guanguan Li; Michael M. Poe; James M. Cook; Matthew L. Banks; S. Stevens Negus (Psychopharmacology, 2017)

“The river is us; the river is in our veins”: re-defining river restoration in three Indigenous communities - Coleen A. Fox; Nicholas James Reo; Dale A. Turner; JoAnne Cook; Frank Dituri; Brett Fessell; James Jenkins; Aimee Johnson; Terina M. Rakena; Chris Riley; Ashleigh Turner; Julian Williams; et al. (Sustainability Science, 2017)

Universal screening for Lynch syndrome among patients with colorectal cancer: patient perspectives on screening and sharing results with at-risk relatives - Jessica Ezzell Hunter; Kathleen A. Arnold; Jennifer E. Cook; Jamilyn Zepp; Marian J. Gilmore; Alan F. Rope; James V. Davis; Kellene M. Bergen; Elizabeth Esterberg; Kristin R. Muessig; Susan K. Peterson; Sapna Syngal; et al. (Familial Cancer, 2017)

Effects of Elevated CO2 on the Swainsonine Chemotypes of Astragalus lentiginosus and Astragalus mollissimus - Daniel Cook; Dale R. Gardner; James A. Pfister; Clinton A. Stonecipher; Joseph G. Robins; Jack A. Morgan (Journal of Chemical Ecology, 2017)

Bioethanol Production from Brewers Spent Grains Using a Fungal Consolidated Bioprocessing (CBP) Approach - Stuart Wilkinson; Katherine A. Smart; Sue James; David J. Cook (BioEnergy Research, 2017)

Groundwater age, mixing and flow rates in the vicinity of large open pit mines, Pilbara region, northwestern Australia - Peter Cook; Shawan Dogramaci; James McCallum; Joanne Hedley (Hydrogeology Journal, 2017)

Codivergence of the primary bacterial endosymbiont of psyllids versus host switches and replacement of their secondary bacterial endosymbionts - Aidan A. G. Hall; Jennifer L. Morrow; Caroline Fromont; Martin J. Steinbauer; Gary S. Taylor; Scott N. Johnson; James M. Cook; Markus Riegler (Environmental Microbiology, 2016)
Summary Coevolution between insects and bacterial endosymbionts contributes to the success of many insect lineages. For the first time, we tested for phylogenetic codivergence across multiple taxonomic scales, from within genera to superfamily between 36 psyllid species of seven recognised families (Hemiptera: Psylloidea), their exclusive primary endosymbiont Carsonella and more diverse secondary endosymbionts (S‐endosymbionts). Within Aphalaridae, we found that Carsonella and S‐endosymbionts were fixed in one Glycaspis and 12 Cardiaspina populations. The dominant S‐endosymbiont was Arsenophonus , while Sodalis was detected in one Cardiaspina species. We demonstrated vertical transmission for Carsonella and Arsenophonus in three Cardiaspina species. We found strong support for strict cospeciation and validated the informative content of Carsonella as extended host genome for inference of psyllid relationships. However, S‐endosymbiont and host phylogenies were incongruent, and displayed signs of host switching and endosymbiont replacement. The high incidence of Arsenophonus in psyllids and other plant sap‐feeding Hemiptera may be due to repeated host switching within this group. In two psyllid lineages, Arsenophonus and Sodalis genes exhibited accelerated evolutionary rates and AT‐biases characteristic of long‐term host associations. Together with strict vertical transmission and 100% prevalence within host populations, our results suggest an obligate, and not facultative, symbiosis between psyllids and some S‐endosymbionts.

One step ahead: a parasitoid disperses farther and forms a wider geographic population than its fig wasp host - Timothy L. Sutton; Markus Riegler; James M. Cook (Molecular Ecology, 2016)
The structure of populations across landscapes influences the dynamics of their interactions with other species. Understanding the geographic structure of populations can thus shed light on the potential for interacting species to co‐evolve. Host–parasitoid interactions are widespread in nature and also represent a significant force in the evolution of plant–insect interactions. However, there have been few comparisons of population structure between an insect host and its parasitoid. We used microsatellite markers to analyse the population genetic structure of Pleistodontes imperialis sp. 1, a fig‐pollinating wasp of Port Jackson fig ( Ficus rubiginosa ), and its main parasitoid, Sycoscapter sp. A, in eastern Australia. Besides exploring this host–parasitoid system, our study also constitutes, to our knowledge, the first study of population structure in a nonpollinating fig wasp species. We collected matched samples of pollinators and parasitoids at several sites in two regions separated by up to 2000 km. We found that pollinators occupying the two regions represent distinct populations, but, in contrast, parasitoids formed a single population across the wide geographic range sampled. We observed genetic isolation by distance for each species, but found consistently lower F ST and R ST values between sites for parasitoids compared with pollinators. Previous studies have indicated that pollinators of monoecious figs can disperse over very long distances, and we provide the first genetic evidence that their parasitoids may disperse as far, if not farther. The contrasting geographic population structures of host and parasitoid highlight the potential for geographic mosaics in this important symbiotic system.

Projected changes in Malawi’s growing season - Edward K. Vizy; Kerry H. Cook; James Chimphamba; Brent McCusker (Climate Dynamics, 2015)

Nitrogen loads explain primary productivity in estuaries at the ecosystem scale - Ryan J. Woodland; James R. Thomson; Ralph Mac Nally; Paul Reich; Victor Evrard; Fiona Y. Wary; Jeffrey P. Walker; Perran L. M. Cook (Limnology and Oceanography, 2015)
Increased nutrient loads stimulate estuary primary productivity and can alter the structure and function of biological communities within estuaries, particularly when producer groups respond differently to changes in nutrient availability. Here, the relative influence of riverine inputs of nitrogen and phosphorus were compared to determine their contribution to estuarine primary producers at large spatial scales. Indices of demersal (extent of macroalgae relative to other vegetation, total shallow water area vegetated) and planktonic (seasonally averaged chlorophyll concentration) primary producer communities were derived at whole‐of‐ecosystem scales in 14 estuaries dispersed across a longitudinal gradient using aerial imaging, underwater videography and in situ monitoring. A model selection framework was used to relate annual nutrient loads (total nitrogen [TN], dissolved inorganic nitrogen [DIN], total phosphorus [TP]), sediment loads (TSS), molar stoichiometric load ratios (TN M : TP M ), and estuary water residence times to the demersal and planktonic indices. Dissolved inorganic nitrogen was the best predictor of the extent of macroalgae, total vegetation coverage, and the concentration of planktonic chlorophyll. Rapid increases in all three indices occurred at inorganic nitrogen loads of ∼ 5–10 Mg km −2 yr −1 . There was some evidence that TN M : TP M , TP and TSS loads were informative model covariates. Relative to DIN loads, TP loads were a poor predictor of the macroalgal and planktonic indices. These findings underscore the critical role of catchment‐derived nitrogen in contributing to producer communities at the whole‐of‐ecosystem scale and support the growing consensus that nitrogen loads (in addition to phosphorus) must be managed to effectively alleviate eutrophication in estuaries.

A characterization of volatile organic compounds and secondary organic aerosol at a mountain site in the Southeastern United States - Michael Link; Yong Zhou; Brett Taubman; James Sherman; Hadi Morrow; Ian Krintz; Luke Robertson; Ryan Cook; Justine Stocks; Matthew West; Barkley C. Sive (Journal of Atmospheric Chemistry, 2015)

Integrating physiological threshold experiments with climate modeling to project mangrove species’ range expansion - Kyle C. Cavanaugh; John D. Parker; Susan C. Cook‐Patton; Ilka C. Feller; A. Park Williams; James R. Kellner (Global Change Biology, 2015)
Predictions of climate‐related shifts in species ranges have largely been based on correlative models. Due to limitations of these models, there is a need for more integration of experimental approaches when studying impacts of climate change on species distributions. Here, we used controlled experiments to identify physiological thresholds that control poleward range limits of three species of mangroves found in North America. We found that all three species exhibited a threshold response to extreme cold, but freeze tolerance thresholds varied among species. From these experiments, we developed a climate metric, freeze degree days ( FDD ), which incorporates both the intensity and the frequency of freezes. When included in distribution models, FDD accurately predicted mangrove presence/absence. Using 28 years of satellite imagery, we linked FDD to observed changes in mangrove abundance in Florida, further exemplifying the importance of extreme cold. We then used downscaled climate projections of FDD to project that these range limits will move northward by 2.2–3.2 km yr −1 over the next 50 years.

‘Double trouble’: the expansion of the Suez Canal and marine bioinvasions in the Mediterranean Sea - Bella S. Galil; Ferdinando Boero; Marnie L. Campbell; James T. Carlton; Elizabeth Cook; Simonetta Fraschetti; Stephan Gollasch; Chad L. Hewitt; Anders Jelmert; Enrique Macpherson; Agnese Marchini; Cynthia McKenzie; et al. (Biological Invasions, 2015)

Development of an In Vitro Model System for Studying Bacterially Expressed dsRNA-Mediated Knockdown in Neoparamoeba genus - Paula C. Lima; Natasha A. Botwright; James O. Harris; Mathew Cook (Marine Biotechnology, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Effect of the duration of inoculum exposure on development of citrus canker symptoms on seedlings of Swingle citrumelo - Clive H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2014)

Convergent structure of multitrophic communities over three continents - Simon T. Segar; Rodrigo A. S. Pereira; Steve G. Compton; James M. Cook (Ecology Letters, 2013)
Astract Ecological theory predicts that communities using the same resources should have similar structure, but evolutionary constraints on colonisation and niche shifts may hamper such convergence. Multitrophic communities of wasps exploiting fig fruits, which first evolved about 75 MYA , do not show long‐term ‘inheritance’ of taxonomic (lineage) composition or species diversity. However, communities on three continents have converged ecologically in the presence and relative abundance of five insect guilds that we define. Some taxa fill the same niches in each community (phylogenetic niche conservatism). However, we show that overall convergence in ecological community structure depends also on a combination of niche shifts by resident lineages and local colonisations of figs by other insect lineages. Our study explores new ground, and develops new heuristic tools, in combining ecology and phylogeny to address patterns in the complex multitrophic communities of insect on plants, which comprise a large part of terrestrial biodiversity.

Insights into functional pharmacology of α1 GABAA receptors: how much does partial activation at the benzodiazepine site matter? - Srđan Joksimović; Zdravko Varagic; Jovana Kovačević; Michael Van Linn; Marija Milić; Sundari Rallapalli; Tamara Timić; Werner Sieghart; James M. Cook; Miroslav M. Savić (Psychopharmacology, 2013)

Molecular Characterization of Mutant Mouse Strains Generated from the EUCOMM/KOMP-CSD ES Cell Resource - Edward Ryder; Diane Gleeson; Debarati Sethi; Sapna Vyas; Evelina Miklejewska; Priya Dalvi; Bishoy Habib; Ross Cook; Matthew Hardy; Kalpesh Jhaveri; Joanna Bottomley; Hannah Wardle-Jones; et al. (Mammalian Genome, 2013)

Greater impulsivity is associated with decreased brain activation in obese women during a delay discounting task - Luke E. Stoeckel; Donna L. Murdaugh; James E. Cox; Edwin W. Cook; Rosalyn E. Weller (Brain Imaging and Behavior, 2013)

Role of gamma-aminobutyric acid type A (GABAA) receptor subtypes in acute benzodiazepine physical dependence-like effects: evidence from squirrel monkeys responding under a schedule of food presentation - Bradford D. Fischer; Laura P. Teixeira; Michael L. van Linn; Ojas A. Namjoshi; James M. Cook; James K. Rowlett (Psychopharmacology, 2013)

Effects of the benzodiazepine GABAA α1-preferring ligand, 3-propoxy-β-carboline hydrochloride (3-PBC), on alcohol seeking and self-administration in baboons - Barbara J. Kaminski; Michael L. Van Linn; James M. Cook; Wenyuan Yin; Elise M. Weerts (Psychopharmacology, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Summary Workshop Report: Facilitating Oral Product Development and Reducing Regulatory Burden Through Novel Approaches to Assess Bioavailability/Bioequivalence - James E. Polli; Jack A. Cook; Barbara M. Davit; Paul A. Dickinson; Domenick Argenti; Nancy Barbour; Alfredo García-Arieta; Jean-Marie Geoffroy; Kerry Hartauer; Shoufeng Li; Amitava Mitra; Francis X. Muller; et al. (The AAPS Journal, 2012)

Improved statistical prediction of surface currents based on historic HF-radar observations - Sergey Frolov; Jeffrey Paduan; Michael Cook; James Bellingham (Ocean Dynamics, 2012)

Barramundi (Lates calcarifer) desaturase with Δ6/Δ8 dual activities - Wei-Chun Tu; Rebecca J. Cook-Johnson; Michael J. James; Beverly S. Mühlhäusler; David A. J. Stone; Robert A. Gibson (Biotechnology Letters, 2012)

Wasting disease regulates long-term population dynamics in a threatened seagrass - James C. Bull; Emma J. Kenyon; Kevan J. Cook (Oecologia, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Lifelong CRF overproduction is associated with altered gene expression and sensitivity of discrete GABAA and mGlu receptor subtypes - Christiaan H. Vinkers; Hendrikus Hendriksen; Ruud van Oorschot; James M. Cook; Sundari Rallipalli; Shengming Huang; Mark J. Millan; Berend Olivier; Lucianne Groenink (Psychopharmacology, 2012)

Influence of Phenological Stage on Swainsonine and Endophyte Concentrations in Oxytropis sericea - Daniel Cook; Lei Shi; Dale R. Gardner; James A. Pfister; Daniel Grum; Kevin D. Welch; Michael H. Ralphs (Journal of Chemical Ecology, 2012)

An Open Source Multivariate Framework for n-Tissue Segmentation with Evaluation on Public Data - Brian B. Avants; Nicholas J. Tustison; Jue Wu; Philip A. Cook; James C. Gee (Neuroinformatics, 2011)

Transient Supplementation of Anabolic Growth Factors Rapidly Stimulates Matrix Synthesis in Engineered Cartilage - Kenneth W. Ng; Christopher J. O’Conor; Lindsay E. Kugler; James L. Cook; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2011)

A Methodology for the Assessment of Unconventional (Continuous) Resources with an Application to the Greater Natural Buttes Gas Field, Utah - Ricardo A. Olea; Troy A. Cook; James L. Coleman (Natural Resources Research, 2010)

Meeting Report: Applied Biopharmaceutics and Quality by Design for Dissolution/Release Specification Setting: Product Quality for Patient Benefit - Arzu Selen; Maria T. Cruañes; Anette Müllertz; Paul A. Dickinson; Jack A. Cook; James E. Polli; Filippos Kesisoglou; John Crison; Kevin C. Johnson; Gordon T. Muirhead; Timothy Schofield; Yi Tsong (The AAPS Journal, 2010)

Wind speed and wind-associated leaf injury affect severity of citrus canker on Swingle citrumelo - C. H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2010)

Obituary: Ross H. Crozier (1943–2009) - James Cook; Ben Oldroyd (Ecology Letters, 2010)

Validation of yellowedge grouper, Epinephelus flavolimbatus, age using nuclear bomb-produced radiocarbon - Melissa Cook; Gary R. Fitzhugh; James S. Franks (Environmental Biology of Fishes, 2009)

Swainsoninine Concentrations and Endophyte Amounts of Undifilum oxytropis in Different Plant Parts of Oxytropis sericea - Daniel Cook; Dale R. Gardner; Michael H. Ralphs; James A. Pfister; Kevin D. Welch; Benedict T. Green (Journal of Chemical Ecology, 2009)

Dissociating anxiolytic and sedative effects of GABAAergic drugs using temperature and locomotor responses to acute stress - Christiaan H. Vinkers; Marianne Klanker; Lucianne Groenink; S. Mechiel Korte; James M. Cook; Michael L. Van Linn; Seth C. Hopkins; Berend Olivier (Psychopharmacology, 2009)

Accountability, Reporting, or Management Improvement? Development of a State of the Parks Assessment System in New South Wales, Australia - Marc Hockings; Carly N. Cook; R. W. Carter; Robyn James (Environmental Management, 2009)

The Biogeographical Distribution of Duncecap Larkspur (Delphinium occidentale) Chemotypes and Their Potential Toxicity - Daniel Cook; Dale R. Gardner; James A. Pfister; Kevin D. Welch; Benedict T. Green; Stephen T. Lee (Journal of Chemical Ecology, 2009)

Glutamatergic and GABAergic modulations of ultrasonic vocalizations during maternal separation distress in mouse pups - Aki Takahashi; Jasmine J. Yap; Dawnya Zitzman Bohager; Sara Faccidomo; Terry Clayton; James M. Cook; Klaus A. Miczek (Psychopharmacology, 2009)

Contribution of α1 subunit-containing γ-aminobutyric acidA (GABAA) receptors to motor-impairing effects of benzodiazepines in squirrel monkeys - Stephanie C. Licata; Donna M. Platt; James M. Cook; Michael L. Van Linn; James K. Rowlett (Psychopharmacology, 2009)

Transcriptome Analyses of Amoebic Gill Disease-affected Atlantic Salmon (Salmo salar) Tissues Reveal Localized Host Gene Suppression - James W. Wynne; Maree G. O’Sullivan; Mathew T. Cook; Glenn Stone; Barbara F. Nowak; David R. Lovell; Nicholas G. Elliott (Marine Biotechnology, 2008)

Summary Workshop Report: Bioequivalence, Biopharmaceutics Classification System, and Beyond - James E. Polli; Bertil S. I. Abrahamsson; Lawrence X. Yu; Gordon L. Amidon; John M. Baldoni; Jack A. Cook; Paul Fackler; Kerry Hartauer; Gordon Johnston; Steve L. Krill; Robert A. Lipper; Waseem A. Malick; et al. (The AAPS Journal, 2008)

Management of resident plant growth-promoting rhizobacteria with the cropping system: a review of experience in the US Pacific Northwest - R. James Cook (European Journal of Plant Pathology, 2007)

Genotyping of phenotypically defined cells in neoplasia: enhanced immunoFISH via tyramide signal amplification (TSA) segregates immunophenotypically—defined cell populations for gated genotyping - Raymond R. Tubbs; Kingshuk Das; James R. Cook; James D. Pettay; Patrick C. Roche; Thomas Grogan (Journal of Molecular Histology, 2007)

The specificity of interphase FISH translocation probes in formalin fixed paraffin embedded tissue sections is readily assessed using automated staining and scoring of tissue microarrays constructed from murine xenografts - Raymond R. Tubbs; James Pettay; Todd S. Barry; Eric Swain; Margaret Loftus; James R. Cook; Marek Skacel; Gillian Paine; Patrick Roche; Thomas Grogan (Journal of Molecular Histology, 2007)

Enhanced sucrose pellet consumption induced by benzodiazepine-type drugs in squirrel monkeys: role of GABAA receptor subtypes - Angela N. Duke; Donna M. Platt; James M. Cook; Shengming Huang; Wenyuan Yin; Bruce A. Mattingly; James K. Rowlett (Psychopharmacology, 2006)

Beaked whale auditory evoked potential hearing measurements - Mandy L. H. Cook; René A. Varela; Juli D. Goldstein; Stephen D. McCulloch; Gregory D. Bossart; James J. Finneran; Dorian Houser; David A. Mann (Journal of Comparative Physiology A, 2006)

Bidirectional effects of benzodiazepine binding site ligands on active avoidance acquisition and retention: differential antagonism by flumazenil and β-CCt - Miroslav M. Savić; Dragan I. Obradović; Nenad D. Ugrešić; James M. Cook; P. V. V. S. Sarma; Dubravko R. Bokonjić (Psychopharmacology, 2005)

Benzodiazepines and heightened aggressive behavior in rats: reduction by GABAA/?1 receptor antagonists - Shannon L. Gourley; Joseph F. DeBold; Wenyuan Yin; James Cook; Klaus A. Miczek (Psychopharmacology, 2005)

Development of Selective Ligands for Benzodiazepine Receptor Subtypes by Manipulating the Substituents at Positions 3- and 7- of Optically Active BzR Ligands - Xiaoyan Li; Jianming Yu; John R. Atack; James M. Cook (Medicinal Chemistry Research, 2004)

A high affinity ligand for GABA A -receptor containing a 5 subunit antagonizes ethanol?s neurobehavioral effects in Long-Evans rats - Peter F. McKay; Katrina L. Foster; Dynesha Mason; Shannan McCane; Xiaohui He; Harry L. June; James M. Cook; Rancia Cummings; Marin Garcia; La Shone Williams; Collette Grey (Psychopharmacology, 2004)

GABAA/α1 receptor agonists and antagonists: effects on species-typical and heightened aggressive behavior after alcohol self-administration in mice - Rosa M. M. de Almeida; James K. Rowlett; James M. Cook; Wenyuan Yin; Klaus A. Miczek (Psychopharmacology, 2004)

Selective antagonism of the ataxic effects of zolpidem and triazolam by the GABA A /α 1 -preferring antagonist β-CCt in squirrel monkeys - Donna Platt; James Rowlett; Roger Spealman; James Cook; Chunrong Ma (Psychopharmacology, 2002)

Role of GABA A /benzodiazepine receptors containing α 1 and α 5 subunits in the discriminative stimulus effects of triazolam in squirrel monkeys - Snjezana Lelas; James Rowlett; Roger Spealman; James Cook; Chunrong Ma; Xiaoyan Li; Wenyuan Yin (Psychopharmacology, 2002)

Different types of GABA A receptors may mediate the anticonflict and response rate-decreasing effects of zaleplon, zolpidem, and midazolam in squirrel monkeys - Carol Paronis; Eric Cox; James Cook; Jack Bergman (Psychopharmacology, 2001)

Sex allocation and local mate competition in Old World non-pollinating fig wasps - Mark D. E. Fellowes; Steve G. Compton; James M. Cook (Behavioral Ecology and Sociobiology, 1999)

Evidence of deep circulation in two perennially ice‐covered Antarctic lakes - Scott W. Tyler; Peter G. Cook; Anya Z. Butt; James M. Thomas; Peter T. Doran; W. Berry Lyons (Limnology and Oceanography, 1998)
The perennial ice covers found on many of the lakes in the McMurdo Dry Valley region of the Antarctic have been postulated to severely limit mixing and convective turnover of these unique lakes. In this work, we utilize chlorofluorocarbon (CFC) concentration profiles from Lakes Hoare and Fryxell in the McMurdo Dry Valley to determine the extent of deep vertical mixing occurring over the last 50 years. Near the ice‐water interface, CFC concentrations in both lakes were well above saturation, in accordance with atmospheric gas supersaturations resulting from freezing under the perennial ice covers. Evidence of mixing throughout the water column at Lake Hoare was confirmed by the presence of CFCs throughout the water column and suggests vertical mixing times of 20–30 years. In Lake Fryxell, CFC‐11, CFC‐12, and CFC‐113 were found in the upper water column; however, degradation of CFC‐ 11 and CFC‐ 12 in the anoxic bottom waters appears to be occurring with CFC‐ 113 only present in these bottom waters. The presence of CFC‐113 in the bottom waters, in conjunction with previous work detecting tritium in these waters, strongly argues for the presence of convective mixing in Lake Fryxell. The evidence for deep mixing in these lakes may be an important, yet overlooked, phenomenon in the limnology of perennially icecovered lakes.

An evaluation of randomization models for nested species subsets analysis - Rosamonde R. Cook; James F. Quinn (Oecologia, 1998)

Reduced Systemic Availability of an Antiarrhythmic Drug, Bidisomide, with Meal Co-administration: Relationship with Region-Dependent Intestinal Absorption - Li-Heng Pao; Simon Yuji Zhou; Chyung Cook; Tugrul Kararli; Carol Kirchhoff; James Truelove; Aziz Karim; David Fleisher (Pharmaceutical Research, 1998)

Unusually low carbon isotope ratios in plants from hanging gardens in southern Utah - Lawrence B. Flanagan; Craig S. Cook; James R. Ehleringer (Oecologia, 1997)

Difference in metabolic profile of potassium canrenoate and spironolactone in the rat: Mutagenic metabolites unique to potassium canrenoate - Chyung S. Cook; Charles L. Hauswald; Grant L. Schoenhard; Charles E. Piper; Arun Patel; Frederick M. Radzialowski; Jeremy D. Hribar; William Aksamit; Pat Finnegan; Roy H. Bible; James A. Oppermann (Archives of Toxicology, 1988)